2021
DOI: 10.1016/j.jtho.2020.11.006
|View full text |Cite
|
Sign up to set email alerts
|

YAP1 Expression in SCLC Defines a Distinct Subtype With T-cell–Inflamed Phenotype

Abstract: Introduction: The clinical and biological significance of the newly described SCLC subtypes, SCLC-A, SCLC-N, SCLC-Y, and SCLC-P, defined by the dominant expression of transcription factors ASCL1, NeuroD1, YAP1, and POU2F3, respectively, remain to be established. Methods:We generated new RNA sequencing expression data from a discovery set of 59 archival tumor samples of neuroendocrine tumors and new protein expression data by immunohistochemistry in 99 SCLC cases. We validated the findings from this discovery s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
95
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(108 citation statements)
references
References 26 publications
11
95
2
Order By: Relevance
“…[14] For clinical relevance, the putative SCLC-Y subtype was found associated with the inflamed phenotype which might be more likely to benefit from immunotherapy. [30] However, Baine's study based on IHC failed to corroborate that YAP1 represented a distinct subtype in SCLC since YAP1 expression was widely distributed in all subtypes. [31] Furthermore, study by Gay et al also confirmed YAP1 did not exclusively define a subtype.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…[14] For clinical relevance, the putative SCLC-Y subtype was found associated with the inflamed phenotype which might be more likely to benefit from immunotherapy. [30] However, Baine's study based on IHC failed to corroborate that YAP1 represented a distinct subtype in SCLC since YAP1 expression was widely distributed in all subtypes. [31] Furthermore, study by Gay et al also confirmed YAP1 did not exclusively define a subtype.…”
Section: Discussionmentioning
confidence: 98%
“…There was no significant difference in other clinical parameters including tumor laterality, clinical stage, VALSG stage, treatment modes and patterns of relapse. As for pathological features, we found a significant higher percentage of necrosis in YAP1 positive group with median [IQR] 30 [20,40] vs. 20 [10,30] in YAP1 positive group and negative group respectively (Table 1). Consistent with these results, we observed that the positive rate of YAP1 was significant higher in the small cell components of C-SCLC (C-SCLC vs. P-SCLC, 52.2% vs. 29.1%, P=0.004), male sex (male vs. female, 37.6% vs. 20.7%, P=0.007), patients with age above 60 (age > 60 vs. age≤60, 43.1% vs. 26.6%, P=0.005) and smokers (yes vs. no: 36.9% vs. 24.5%, P=0.042) (Table 2).…”
Section: Yap1 Histological Location and Clinicopathological Relevancementioning
confidence: 93%
“…54 This new classification may have therapeutic implications, and the SCLC-Y subtype is enriched for T-cell inflamed phenotype, high expression of IFN-g response genes and longterm survival, predicting potential clinical benefit of immunotherapy in this subtype. 55 Recently, using RNAseq analysis, it was reported that the distribution of subtypes from the phase III IMpower133 trial was 51% SCLC-A, 23% SCLC-N, 18% SCLC-I inflamed and 7% SCLC-P. Although the trial was not statistically powered for subtype-specific subgroup analyses, the addition of atezolizumab improved the OS across all four subtypes, including a modest trend toward improved OS in SCLC-I relative to each of the other three subtypes that is not observed in the placebo arm.…”
Section: Limited Efficacy Of Icis In Sclcmentioning
confidence: 99%
“…Some investigators have further explored the association between YAP1 and immunity. Owonikoko et al ( 28 ) found that SCLCs with YAP1 positive was enriched in long-term survivors, and associated with high expression levels of interferon-γ ( INF-γ ) gene, human leukocyte antigen ( HLA ) gene, and T-cell receptor gene, and high scores of T-cell inflammatory gene expression profile (GEP). They subsequently replicated this inflammatory phenotype using SCLC cell lines and tumor samples in two independent validation datasets ( 28 ).…”
Section: Transformation In Molecular Typing Of Sclcsmentioning
confidence: 99%
“…Owonikoko et al ( 28 ) found that SCLCs with YAP1 positive was enriched in long-term survivors, and associated with high expression levels of interferon-γ ( INF-γ ) gene, human leukocyte antigen ( HLA ) gene, and T-cell receptor gene, and high scores of T-cell inflammatory gene expression profile (GEP). They subsequently replicated this inflammatory phenotype using SCLC cell lines and tumor samples in two independent validation datasets ( 28 ). Similarly, another study revealed that although SCLC is a cancer with the lowest expression of immune-related genes, SCLC-Y cell lines evidently show a tendency for better antigenic presentation and innate immune response.…”
Section: Transformation In Molecular Typing Of Sclcsmentioning
confidence: 99%